Evaluation of the first pharmacist-administered vaccinations in Western Australia: a mixed-methods study. Issue 9 (20th September 2016) - Hattingh, H Laetitia; Sim, T Fei; Parsons, R; Czarniak, P; Vickery, A; Ayadurai, S
Abstract : Objectives: This study evaluated the uptake of Western Australian (WA) pharmacist vaccination services, the profiles of consumers being vaccinated and the facilitators and challenges experienced by pharmacy staff in the preparation, implementation and delivery of services. Design: Mixed-methods methodology with both quantitative and qualitative data through surveys, pharmacy computer records and immuniser pharmacist interviews. Setting: Community pharmacies in WA that provided pharmacist vaccination services between March and October 2015. Participants: Immuniser pharmacists from 86 pharmacies completed baseline surveys and 78 completed exit surveys; computer records from 57 pharmacies; 25 immuniser pharmacists were interviewed. Main outcome measures: Pharmacy and immuniser pharmacist profiles; pharmacist vaccination services provided and consumer profiles who accessed services. Results: 15 621 influenza vaccinations were administered by immuniser pharmacists at 76 WA community pharmacies between March and October 2015. There were no major adverse events, and <1% of consumers experienced minor events which were appropriately managed. Between 12% and 17% of consumers were eligible to receive free influenza vaccinations under the National Immunisation Program but chose to have it at a pharmacy. A high percentage of vaccinations was delivered in rural and regional areas indicating that provision of pharmacist vaccination services facilitated access for rural and remote consumers. Immuniser pharmacists reported feeling confident in providing vaccination services and were of the opinion that services should be expanded to other vaccinations. Pharmacists also reported significant professional satisfaction in providing the service. All participating pharmacies intended to continue providing influenza vaccinations in 2016. Conclusions: This initial evaluation of WA pharmacist vaccination services showed that vaccine delivery was safe. Convenience and accessibility were important aspects in usage of services. There is scope to expand pharmacist vaccination services to other vaccines and younger children; however, government funding to pharmacists needs to be considered.